Ipsi- and contralateral interaction in the 40 Hz auditory steady state responses (ASSRs) with two carriers at 60 dB SPL - Papakonstantinou, Alexandra; Kollmeier, Birger; Riedel, Helmut (International journal of audiology, 2013)
Objective: Auditory steady state responses have been suggested for simultaneous threshold assessment using the multiple ASSR (MASSR) technique. However, at least at high stimulation levels, strong interactions reduce response amplitudes. The present study investigates ASSR interaction at a moderate stimulus level. Design: Sinusoidal carriers modulated at rates near 40 Hz were used as probe. Unmodulated and modulated interferers were presented ipsi- or contralaterally. Study sample: Twenty normal-hearing subjects participated. Results: Unmodulated interferers did not significantly change ASSR amplitudes. Modulated interferers, presented ipsilaterally or contralaterally, both significantly reduced the ASSR SNR by 13% and 8%, respectively. Conclusions: To compensate for the average SNR reduction would require a 32% and 18% longer measurement time for ipsi- and contralateral interferers, respectively, far less than the doubling of measurement time for two single measurements, emphasizing the MASSR technique advantage. However, the largest reduction for a single subject was 22% for the amplitude and 28% for the SNR, almost completely undoing the benefit in measurement time in MASSR. The individually varying interaction effects even at 60 dB SPL clearly limits the advantage of using the MASSR for modulation rates near 40 Hz over corresponding single ASSR measurements, at least for two simultaneous carriers.